2012
DOI: 10.5936/csbj.201209004
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Engineer Stability of Beetle Luciferases

Abstract: Luciferase enzymes from fireflies and other beetles have many important applications in molecular biology, biotechnology, analytical chemistry and several other areas. Many novel beetle luciferases with promising properties have been reported in the recent years. However, actual and potential applications of wild-type beetle luciferases are often limited by insufficient stability or decrease in activity of the enzyme at the conditions of a particular assay. Various examples of genetic engineering of the enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 68 publications
0
12
0
1
Order By: Relevance
“…6a). Since temperature impacts the enzymatic activity of the luciferase 27 , we first corrected the signal for this systematic effect (Supplementary Information). We found that, independently of initial densities, as the populations reach confluency (which takes longer for initial low density), the phases and amplitudes become stationary, showing 1:1 entrainment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6a). Since temperature impacts the enzymatic activity of the luciferase 27 , we first corrected the signal for this systematic effect (Supplementary Information). We found that, independently of initial densities, as the populations reach confluency (which takes longer for initial low density), the phases and amplitudes become stationary, showing 1:1 entrainment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of the commonly used Photinus phyralis firefly luciferase is considerably higher at reduced temperatures. This effect is attributed to reduced protein activity and a so-called red shift in the luminescence at higher temperatures (for review, see Koksharov and Ugarova 2012). Therefore, we used the more temperature-tolerant mutant Luciola mingrelica firefly luciferase (LMLucR) (Koksharov and Ugarova 2011) for the construction of the Cirbp-luciferase reporter gene.…”
Section: Temperature-dependent Cirbp Mrna Accumulation Is Regulated Bmentioning
confidence: 99%
“…The design of proteins with enhanced thermostability is one of the major goals of protein engineering. Many attempts have been made by site directed mutagenesis to increase thermostability of firefly luciferase [3][4][5].…”
Section: Introductionmentioning
confidence: 99%